Społeczny świat hodowców gołębi pocztowych - Słowińska, Karolina (Przegląd Socjologii Jakościowej, 2010)
The paper is an attempt to describe social world of pigeons breeders. Basic aim was to look into particular aspects which constitute this specific social group in the light of social interactionism and theory of social worlds. The central issues were therefore values within this world, legitimating of commitment in breeders work, the process of becoming pigeons breeder and relations between breeders and their birds. All these issues were described in a wider context of conditions influencing pigeons breeding. Presented findings are based on empirical research conducted among pigeons breeders from one region of Poland between 2006 and 2007. Collected empirical data were analyzed and interpreted according to the rules of grounded theory methodology.